Sinonasal renal cell-like adenocarcinoma arising in von Hippel Lindau (VHL) syndrome. (February 2022) - Maharaj, Satish; Seegobin, Karan; Wakeman, Kristina; Chang, Simone; Potts, Kevin; Williams, Brian; Redman, Rebecca
Highlights: SNRCLA is a rare diagnosis described by the WHO in 2017 as an emerging entity. We report the first confirmed case arising in von Hippel Lindau (VHL) syndrome. A review of the literature revealed two similar cases that support the association. Genomic testing implicates MST1R gene mutation in association with VHL. Abstract: Sinonasal renal cell-like adenocarcinoma (SNRCLA) is a rare and relatively novel diagnosis. Hereditary and somatic genomic signatures are not well defined in this disease. We report the case of a 35-year-old African-American male with von Hippel Lindau (VHL) syndrome who developed SNRCLA. He underwent surgical resection followed by adjuvant radiation and has no recurrence one year from diagnosis. A review of the literature yielded two similar cases in the setting of VHL. In our case with associated VHL syndrome, next generation sequencing detected MST1R mutation, a possible driver. SNRCLA is an emerging tumor associated with VHL syndrome and it is hoped that future studies shed light on the underlying biology of this unique tumor.